Cerebrospinal fluid neurofilament light chain levels in children with acquired demyelinating syndrome - Wu, Wenlin; Hou, Chi; Wu, Wenxiao; Shen, Huiling; Zeng, Yiru; Chen, Lianfeng; Liao, Yinting; Zhu, Haixia; Tian, Yang; Peng, Bingwei; Chen, Wen-Xiong; Li, Xiaojing (Frontiers in Pediatrics, 2024)
Objective: To study the cerebrospinal fluid (CSF) neurofilaments light chain (NfL) in pediatric acquired demyelinating syndrome (ADS) and its association with factors of laboratory and imaging results.: Clinical data of children with ADS from May 2020 to January 2021 in the department of neurology of Guangzhou Women and Children's Medical Center were analyzed. Enzyme-linked immunosorbent assays detected the CSF NfL of patients.Results: Thirty pediatric ADS patients (male: female 17:13) were included. The most frequent diagnosis seen was uncategorized ADS (36.7%, 11/30), followed by ADEM (23.3%, 7/30), MOGAD (20.0%, 6/30), NMO (6.7%, 2/30), MS (6.7%, 2/30) and NMOSD (6.7%, 2/30). The median CSF NfL for the first time was 7425.28 pg/ml (IQR 1273.51, >10000 pg/ml). CSF NfL increase over normal value (<290.00 pg/ml for people younger than 30 years old) was seen in 98.7% of patients. Patients were divided into uncategorized ADS, ADEM group, MOGAD, and MS/NMO/NMOSD group, and no significant difference in CSF NfL between each group. The CSF NfL positively correlated with the immunoglobulin (Ig) G (ρ=0.473) and IgE (ρ=0.366). However, the CSF NfL did not correlate with CSF white blood count and CSF protein. Furthermore, there was no significant difference between patients with oligoclonal bands positive and without. The CSF NfL negatively correlated with IFN-γ (ρ=-0.501), CD45 + CD3 + T (ρ=-0.466), CD45 + CD3 + CD4 + T (ρ=-0.466) cells and CD45 + CD3 + CD8 + T cells (ρ=-0.521). However, it did not correlate with CD45 + CD19 + B cells. CSF NfL in patients with cerebral white matter lesions in MRI was higher than in patients without. Besides, the CSF NfL positively correlated with the number of brain MRI locations(ρ=0.362). Nine patients underwent multiple detections of CSF NfL, and their CSF NfL for the last detection was not significantly different from the first.The CSF NfL increases significantly in pediatric ADS, and it can be a biomarker of neuro-axonal injury and a good indication of the extent of lesions.